2018
DOI: 10.1089/sur.2017.245
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Glucuronidase Inhibition Reduces Severity of Diclofenac-Induced Anastomotic Leak in Rats

Abstract: Microbial glucuronidase inhibitor reduces diclofenac-induced anastomotic leakage severity, which suggests a harmful effect of diclofenac metabolite reactivation in the gut. This finding improves the understanding of the pathogenesis of anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Beyond irinotecan, the intestinal toxicity of NSAIDs, which are also glucuronidated and reactivated by GUS enzymes in the gut, has also been alleviated using targeted microbial GUS inhibitors administered to male and female mice (10,11,34). Inh1 has been shown in rats to reduce nonsteroidal antiinflammatory drug (NSAID)-induced intestinal anastomotic leakage (35). Kong et al (36) have replicated our findings with Inhibitor 1 and have shown that the tricyclic antidepressant amoxapine is a bacterial GUS inhibitor.…”
Section: Discussionsupporting
confidence: 61%
“…Beyond irinotecan, the intestinal toxicity of NSAIDs, which are also glucuronidated and reactivated by GUS enzymes in the gut, has also been alleviated using targeted microbial GUS inhibitors administered to male and female mice (10,11,34). Inh1 has been shown in rats to reduce nonsteroidal antiinflammatory drug (NSAID)-induced intestinal anastomotic leakage (35). Kong et al (36) have replicated our findings with Inhibitor 1 and have shown that the tricyclic antidepressant amoxapine is a bacterial GUS inhibitor.…”
Section: Discussionsupporting
confidence: 61%
“…However, an attempt to reduce the inhibitor's serum exposure for increased GI residence by replacing ethoxy unit with hydroxyl or morpholinyl groups led to inferior pharmacological profile compared to parent compound 151 [226]. Further, compound 152 exerted 2-fold reduction in the severity of diclofenacinduced anastomotic leakage, without affecting drug's plasma concentration in Wistar rats receiving 0.8 mg of the inhibitor and 3 mg/kg of diclofenac [227]. In contrast, rats receiving diclofenac only suffered severe leakage thus suggesting the inhibitor's potential clinical utility to improve anastomotic healing.…”
Section: Coumarins and Azacoumarinsmentioning
confidence: 99%
“…Second, an in-depth evaluation of the level of microbial BGUS inhibition (feces) by UNC10201652 needs to be performed in the MMTV-PyMT mice to determine the extent to which inhibition of all relevant BGUS enzymes occurs at the chosen dose (20 µM/day). It is important to note that this dose was chosen based on prior observations that BGUS inhibition at this dose are effective in vivo across several mouse models [27,28,31,35]. In this context, evaluation of the intestinal and breast microbiota in terms of any major changes in species/class/phyla using 16S or other metagenomic sequencing needs to be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor 1 was found to have no effect on plasma levels of diclofenac in mice [31]. Finally, in 2018, it was shown that Inhibitor 1 blocks anastomotic leakage after intestinal resection in rats given diclofenac [35]. Thus, a potent and specific BGUS inhibitor that does not kill microbial cells has been shown to be effective in blocking several negative outcomes with drugs or surgical…”
Section: Introductionmentioning
confidence: 99%